Patent settlements in the pharmaceutical industry: What can we learn from economic analysis? - Severin Frank; Wolfgang Kerber (Philipps-University Marburg, School of Business and Economics, 2016)
Patent settlements between originator and generic firms in the pharmaceutical industry have been challenged by antitrust and competition authorities in the U.S. and the EU. Particularly settlements with large "reverse payments" to generic firms raise the concern of collusive behaviour for protecting weak patents and delaying price competition through generic entry and therefore harming consumers. However, it is still heavily disputed under what conditions such patent settlements are anticompetitive and violate antitrust rules. This article scrutinizes critically what economic analysis has so far contributed to our knowledge about the effects of these patent settlements and the possible rules for their antitrust treatment. An important claim of this paper is that the problem of patent settlements can only be understood, if we analyze it not only from a narrow antitrust perspective but also take into account its deep interrelationship with the problems (and the economics) of the patent system. Therefore we identify three different channels of effects, how patent settlements can influence consumer welfare: (1) price effects, (2) innovation incentive effects, and (3) effects via the incentives to challenge weak patents. The paper critically analyzes the existing economic studies and identifies a number of research gaps, especially also in regard to trade offs between different effects. It also suggests that policy solutions for these patent settlements should also be sought in combination with patent law solutions.
Keywords: K40; L40; O34; 330; patent settlements; probabilistic patents; weak patents; pharmaceutical industry; generic competition